Molecular Diagnostics of Lung Cancer in Serous Effusion Samples - Jana Fassunke; Reinhard Büttner; Marianne Engels (MDPI AG, 2022)
For molecular diagnostics of lung cancer samples, often only a small amount of material is available. The ever-increasing number of biomarker testing is in contrast to the amount of material obtained. In that case, cytological specimens, such as serous effusion samples, are one possible option. Effusion samples were prepared as sediment smears or cytospins or as a cell block if needed. Suitable tumor cells areas were marked by a cytopathologist and used for molecular diagnostics, including fast track analysis, parallel sequencing, and/or fluorescence in situ hybridization. In 62 cases of malignant effusion with cells of pulmonary adenocarcinoma, molecular diagnostics were carried out. A fast-track result with the high-resolution melting method for hotspot mutation of KRAS Exon 2 and EGFR exon 21 and fragment length analysis of EGFR exon 19 was available for 43 out of 47 samples (92%). Parallel sequencing was successful for 56 out of 60 samples (93.3%). In the same period, 108 FISH analyses were performed for MET amplification, followed by ROS1, RET, and ALK translocation analysis. If only a limited amount of tissue/biopsy is available, a malignant effusion is advisable to perform on the molecular diagnostics with a high success rate.